2019
DOI: 10.3389/fmars.2019.00411
|View full text |Cite|
|
Sign up to set email alerts
|

Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia’s Coast

Abstract: Babcock et al. ECEs Affect 45% Australian Coastline abrupt ecological changes that are caused by ECEs could have greater long-term impacts than slower warming that leads to gradual reorganization and possible evolution and adaptation. ECEs are an emerging threat to marine ecosystems, and will require better seasonal prediction and mitigation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
147
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 123 publications
1
147
0
1
Order By: Relevance
“…For instance, tide pools along the west coast of North America occur in a naturally high‐productivity region influenced by upwelling of cold, high CO 2 /low O 2 ocean water, which influence biogeochemistry in the intertidal (Chan et al, 2017; Silbiger & Sorte, 2018). In contrast, waters off eastern Australia are comparatively oligotrophic (Marshall et al, 2012; Roughan & Middleton, 2002) and are strongly influenced by the warm poleward flow of a major boundary current (Babcock et al, 2019; Oliver et al, 2018; Suthers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, tide pools along the west coast of North America occur in a naturally high‐productivity region influenced by upwelling of cold, high CO 2 /low O 2 ocean water, which influence biogeochemistry in the intertidal (Chan et al, 2017; Silbiger & Sorte, 2018). In contrast, waters off eastern Australia are comparatively oligotrophic (Marshall et al, 2012; Roughan & Middleton, 2002) and are strongly influenced by the warm poleward flow of a major boundary current (Babcock et al, 2019; Oliver et al, 2018; Suthers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Climate change will impact on oyster reef restoration [36]. Projected ocean warming for the region (4°C) as well as contemporary marine heat waves, as seen in the region recently [39] are an important consideration for reef restoration efforts along the south-eastern coastline of Australia. Our study has shown that using thermal outfall as a proxy for ocean warming can be useful for predicting future warming.…”
Section: Discussionmentioning
confidence: 99%
“…South-eastern Australia receives warmer waters from the Coral Sea via the East Australian Current (EAC), which is strengthening [37, 38]. This region is considered a “hot spot”, as the rise in mean temperatures will be 3-4 times higher than the average for the world’s oceans and is also prone to marine heat waves [7,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated water effluents in fresh water are a big challenge for the aquaculture industries. Also, temperature extremes are a serious issue for marine biodiversity [57] .…”
Section: Aquaculturementioning
confidence: 99%
“…These contrast with diet choice, animal health, worker lifestyle, and social and economic conditions, which are considered as non-environmental issues. Food processing has fewer environmental impacts than farming [73] , because processors are regulated by law or respond to their own interest based on reports and surveys from the food chain to reduce inputs, energy, and water that has cost savings advantages and consequent environmental benefits [57] .…”
Section: Food Processingmentioning
confidence: 99%